2001
DOI: 10.1111/j.0901-9928.2001.890407.x
|View full text |Cite
|
Sign up to set email alerts
|

High NaCl Intake Decreases both Flow‐Induced Dilation and Pressure‐Induced Myogenic Tone in Resistance Arteries from Normotensive Rats: Involvement of Cyclooxygenase‐2

Abstract: The effect of high NaCl diet on resistance arteries is not yet fully documented. In order to assess the effect of NaCl on myogenic tone and flow-induced dilation independent of arterial blood pressure change, we used normotensive rats which did not develop hypertension upon high NaCl intake. Normotensive Wistar Kyoto Rats received a high (8%) or a normal NaCl diet (0.4%). Mesenteric resistance arteries (150 mm, internal diameter) were cannulated in an arteriograph to allow perfusion of arteries under controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…Finally, shear stress-dependent NO release can also contribute to the dilation of proximal arterioles during larger increases in metabolic demand [22], and we have found that consumption of a 7% salt diet decreases arteriolar responsiveness to shear stress due to a selective loss of NO activity [7]. This salt-induced attenuation of arteriolar responsiveness to pressure and shear stress has been documented in other vascular beds as well [39,40,41]. Based on the above findings, we postulated in the current study that active hyperemia would be compromised in the contracting spinotrapezius muscle of HS rats.…”
Section: Discussionmentioning
confidence: 70%
“…Finally, shear stress-dependent NO release can also contribute to the dilation of proximal arterioles during larger increases in metabolic demand [22], and we have found that consumption of a 7% salt diet decreases arteriolar responsiveness to shear stress due to a selective loss of NO activity [7]. This salt-induced attenuation of arteriolar responsiveness to pressure and shear stress has been documented in other vascular beds as well [39,40,41]. Based on the above findings, we postulated in the current study that active hyperemia would be compromised in the contracting spinotrapezius muscle of HS rats.…”
Section: Discussionmentioning
confidence: 70%
“…COX products were shown to augment arterial tone in mesenteric arteries by inhibiting nitric oxide synthesis that is decreased in L-NAME-mediated hypertension in rats (4). Furthermore, endothelial COX-2 was shown to be upregulated in mesenteric arteries from rats with high NaCl intake, mediating myogenic tone suggesting a compensatory or protective role of COX-2 in pressure-mechanotransduction (38).…”
Section: Discussionmentioning
confidence: 98%
“…Shear stress is nearly universally associated with vasodilation in the peripheral vasculature, where research has consistently demonstrated a predominant vasodilatory response to blood flow in conduit arteries, such as femoral (205) and carotid (6,15,16,116,156) arteries, as well as resistance arteries and arterioles, including mesenteric arteries (16,23,98,116,123,188,234), coronary arteries (22,54,78,79,90,91,99,101,105,112,113,133,134,178,203,204,236,237), skeletal muscle feed arteries/arterioles (5-7, 55, 77, 86 -89, 96, 97, 166, 171, 180, 186, 187, 189, 190, 196, 202, 208, 228 -230), and adipose arterioles (153). Interestingly, shear stress is clearly capable of causing vasoconstriction in the cerebral circulation (20, 145,201).…”
Section: Mechanosensing In Endothelial Cells: Vasodilationmentioning
confidence: 99%